2020
DOI: 10.3390/ijerph17176178
|View full text |Cite
|
Sign up to set email alerts
|

Lung Health in Children in Sub-Saharan Africa: Addressing the Need for Cleaner Air

Abstract: Air pollution is increasingly recognized as a global health emergency with its impacts being wide ranging, more so for low- and middle-income countries where both indoor and outdoor pollution levels are high. In Africa, more than 80% of children live in households which use unclean sources of energy. The effects of both indoor and outdoor pollution on lung health on children who are the most vulnerable to their effects range from acute lower respiratory tract infections to long-term chronic health effects. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…A very limited number of African studies suggested that traffic- or industry-related air pollution [ 32 , 33 , 34 , 35 , 36 ], which most often occurs in urban areas, was associated with wheeze, cough, allergic rhinitis and phlegm in children. However, most of these studies had only assessed residential proximity to main road, industrial or mine areas rather than individual air pollutants [ 15 , 16 ]. More recently, a study in the Western Cape province found that modelled-NO 2 , but not modelled-PM 2.5 , was significantly associated with a new onset of asthma symptoms among school-aged children residing in informal settlements [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A very limited number of African studies suggested that traffic- or industry-related air pollution [ 32 , 33 , 34 , 35 , 36 ], which most often occurs in urban areas, was associated with wheeze, cough, allergic rhinitis and phlegm in children. However, most of these studies had only assessed residential proximity to main road, industrial or mine areas rather than individual air pollutants [ 15 , 16 ]. More recently, a study in the Western Cape province found that modelled-NO 2 , but not modelled-PM 2.5 , was significantly associated with a new onset of asthma symptoms among school-aged children residing in informal settlements [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a dearth of data for such associations in the SSA region [ 14 ]. Among the limited number of studies in Africa, most have used crude proxies of ambient air pollution (e.g., residential proximity to industrial areas, heavy-traffic roads or mine dumps) instead of individual air pollutants [ 15 , 16 ]. This has largely explained the inconsistent findings across the studies and also inhibited comparisons with studies in which individual air pollutants were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Indoor pollution exposures, primarily through tobacco smoking or the use of biomass cooking fuels, have been shown to impact health in low-income countries [ 3 , 4 ]. Biomass cooking fuels are associated with acute respiratory infections (ARIs) [ 5 ], tuberculosis [ 6 ], COPD [ 7 ], and asthma [ 8 , 9 ]. Less well-understood are the associations between ambient (outdoor) air exposures to pollutants, such as PM and respiratory health in SSA.…”
Section: Introductionmentioning
confidence: 99%
“…Indoor pollution exposures, primarily through tobacco or the use of biomass cooking fuels, have been shown to have impacts on public health in low-income countries [ 28 , 29 ]. In SSA countries, research has shown that indoor cooking using biomass fuels is associated with a number of non-communicable respiratory diseases (NCRDs), including acute respiratory infections [ 30 ], tuberculosis [ 31 ], chronic obstructive pulmonary disease (COPD) [ 32 ], and asthma [ 33 ]. Less well understood, however, are the associations between ambient (outdoor) air exposures and NCRDs in SSA.…”
Section: Introductionmentioning
confidence: 99%